A dissertation on tooth size and arch dimension in uncrowded versus crowded Class I malocclusion (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Aim: The purpose of this investigation was to examine the extent to which arch dimension or tooth size contributes to dental crowding. Materials and Methods: Two groups of dental casts were selected. Each group consisted of 30 pairs of dental casts including equal male and female samples. The first group had Class I malocclusion without crowding. The second group exhibited Class I malocclusion with dental crowding (more than 5 mm space deficiency). The following parameters were measured and used to compare the two groups: individual and collective mesiodistal widths of tooth, dental arch length, as well as buccal and lingual dental arch widths in the canine and molar regions. Results: Statistically significant differences in both tooth widths and transverse arch dimensions (widths) were found between the crowded and the normal groups. The crowded group was found to have a significantly smaller maxillary arch width and larger tooth size when compared with the uncrowded or normal group. There were no significant differences in arch length in the two groups in either the maxilla or the mandible. In comparing the anterior and overall Bolton ratios no significant difference was detected between the crowded and normal groups. Conclusion: The results of this study suggest under under two study groups (Class I skeletal base of crowded and uncrowded group) tooth size has a greater role in developing dental crowding. DOI: http://dx.doi.org/10.3329/bjodfo.v2i1.15994 Ban J Orthod & Dentofac Orthop, October 2011; Vol-2, No.1, 1-6